Non-coding RNAs in gastric cancer immunotherapy: mechanisms and clinical implications - Dong, Haotian; Ye, Chengyuan; Yu, Xuan; Shao, Yongfu (Frontiers in Immunology, 2025)
Gastric cancer immunotherapy, recognized as the fourth primary treatment modality after surgery, radiotherapy, and chemotherapy, encompasses strategies such as immune checkpoint inhibitors and cellular immunotherapy and provides new avenues for cancer control. Recent studies have revealed that non-coding RNAs (ncRNAs), including miRNAs, lncRNAs, piRNAs, siRNAs, and circRNAs, drive the progression of gastric cancer primarily through three regulatory axes: epigenetic modification, transcriptional reprogramming, and tumor microenvironment remodeling. These processes are closely linked to tumor immunity and the efficacy of immunotherapy in gastric cancer (GC). Building on an overview of current immunotherapy regimens for GC, this review provides a comprehensive summary of the molecular mechanisms by which ncRNAs regulate immune cell infiltration, modulate immune checkpoints, and reshape the immunosuppressive microenvironment to influence immunotherapeutic outcomes. Furthermore, the potential translational applications of ncRNAs as prognostic biomarkers and therapeutic targets within the context of GC immunology are discussed. Collectively, these mechanistic insights and clinical perspectives offer a theoretical foundation for overcoming the limitations of current immunotherapy approaches and improving the long-term prognosis of patients with GC.